Study on Functional Anatomy of Tongue in Domestic Animals - Hamid, Asadullah (Journal of Natural Sciences – Kabul University, 2022)
The tongue is an important organ composed of skeletal muscle that occupies most of the oral cavity. The functions of the tongue include drinking water, food intake, mixing food in the mouth, swallowing, mastication, and speech in humans. It is also the primary organ of taste, containing taste buds on its dorsal surface. In dogs, the tongue plays a role in thermoregulation by reducing body temperature through panting. The body of the tongue is connected to the floor of the mouth via the frenulum. This study measured and compared different parts of the tongue in domestic animals and chickens, examining specific anatomical features in various domestic animals. Simple tools such as rulers and measuring tapes were employed for these measurements. The results show that the anatomy and various parts of the tongue differ among species depending on their diet and feeding habits.